Analisis Harapan Dan Persepsi Konsumen Terhadap Kualitas Produk (Studi Kasus Pada Toko Aksesoris "X" Di Pakuwon Trade Center, Surabaya) - Evi Thelia Sari; Hendry Setyono . (Jurnal Manajemen Maranatha, 2011)
This research is to measure the level of product quality expectations, services and prices to meet the consumers' perception. This research used Gap analysis. The object of this research is specified for Toko aksesoris "X"'s consumers at Pakuwon Trade Centre, Surabaya with a total of 94 respondents and sampling method in this research is convenience sampling. Primary data is taken from the respondents. The result of Gap Analysis shows that product quality on the first quadrant, Toko aksesoris "X" is preparing a ready stock for consumers so they can always choose and order any products that are suitable with their needs at that moment. The result of the study shows that there is Gap Differentiation between expectation and perception of consumers towards product quality at Toko aksesoris "X" in Pakuwon Trade Centre Surabaya.Keywords: Gap analysis, Product quality, perception, expectation